Interview with Alya Guseva: How Markets for Credit Cards were Created in Postcommunist Societies - Alya Guseva (Journal of Economic Sociology, 2015)
Alya Guseva, Professor of Sociology at Boston University, was interviewed by Natalia Khalina, a Lecturer at the Higher School of Economics. The interview was conducted during the workshop “Consumption and Economic Crises: Post-Socialist Experiences” (Moscow, 9–10 October 2014) where A. Guseva presented her new book “Plastic Money: Constructing Markets for Credit Cards in Eight Postcommunist Countries”, co-authored with A. Rona-Tas [Rona-Tas, Guseva 2014]. In the interview Guseva describes how markets for credit cards became the subject of her research interest and why card markets in Poland, Hungary, The Czech Republic, Bulgaria, Russia, Ukraine, China and Vietnam were chosen for the study. Guseva explains how these markets were constructed and how successful the listed countries were in reproducing the “American credit card market” model. Two key concepts of the book, concerning market creation and market operation, were considered: functional rules and generative rules and how postcommunist market actors applied those rules. Additionally, questions concerning how bank cards change family finance practices and how bank card usage, connected with power and control for information and resources, were raised. At the end of her interview Guseva points out that while we are observing the creation of credit card markets within postcommunist space, the credit card markets themselves are being pressed by the emerging market of mobile payments.